(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
Baburnama, a unique and remarkable example of Uzbek prose of the 16th century, encompasses knowledge from many fields of science. Japanese scholar Eiji Mano describes it as “a treasury of information on the Uzbek language and on Central Asia, Afghanistan, and India in the 15th–16th centuries” [1, pp. 19]. Among the works that provide vivid testimony about ancient Transoxiana (Mawarannahr) and the life of its peoples, Baburnama stands out distinctly. Created by Zahiriddin Muhammad Babur—an outstanding lyric poet and a representative of Uzbek classical literature after Alisher Navoi—this work is truly a rich source of socio-historical, natural-scientific, and literary-linguistic information. It describes events that took place in Central Asia, Afghanistan, and India from 1494 to 1530. In Baburnama, the prominent statesman Zahiriddin Muhammad Babur provides detailed accounts of the history, socio-economic conditions, nature, ethnography, geography, and even medicine of the Fergana Valley, Afghanistan, and India. In particular, he presents precise information about the mountains of Fergana and India, the rivers originating from them, as well as forests, pastures, gardens, flora, and fauna, often comparing these data with one another.